2012
DOI: 10.1002/gps.3888
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life events and cognitive decline in late life: moderation by education and age. The Cache County Study

Abstract: Objective Stressful life events (SLE) have been associated with increased dementia risk, but their association with cognitive decline has been inconsistent. In a longitudinal population-based study of elderly individuals, we examined the association between SLE and cognitive decline, and the role of potential effect modifiers. Methods A total of 2665 non-demented participants of the Cache County Memory Study completed a stress life events questionnaire at Wave 2, and were revisited 4 and 7 years later. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 37 publications
4
32
0
1
Order By: Relevance
“…For example, Peavy and colleagues (2009) reported that higher amounts of cumulative stressful experiences over the course of three years resulted in decreased working memory performance among a sample of elderly individuals suffering from mild cognitive impairment. Similar findings are reported by a number of cross-sectional studies which state that higher amounts of cumulative stressful events coincide with reduced working memory performance among healthy elderly participants (Dickinson et al, 2011;Tschanz et al, 2012). In addition, rencently published work (Marshall, Cooper, Segrave & Geeraert, 2015) established an inverse relationship between the amount of cumulative experienced stress and cognitive working memory performance among elderly individuals, which was not present among young control participants.…”
Section: Introductionsupporting
confidence: 85%
“…For example, Peavy and colleagues (2009) reported that higher amounts of cumulative stressful experiences over the course of three years resulted in decreased working memory performance among a sample of elderly individuals suffering from mild cognitive impairment. Similar findings are reported by a number of cross-sectional studies which state that higher amounts of cumulative stressful events coincide with reduced working memory performance among healthy elderly participants (Dickinson et al, 2011;Tschanz et al, 2012). In addition, rencently published work (Marshall, Cooper, Segrave & Geeraert, 2015) established an inverse relationship between the amount of cumulative experienced stress and cognitive working memory performance among elderly individuals, which was not present among young control participants.…”
Section: Introductionsupporting
confidence: 85%
“…The authors proposed that it may be the stressful events that contribute to the cognitive decline (Kozora, Ellison, & West, 2009). This is supported by research into the effect of stressful life events on cognitive decline in elderly populations, although mediating factors such as age and education level also play a role (Tschanz et al, 2013). An earlier study that assessed the relationship between stress, as measured by daily hassles, in PwMS, found that being female, younger, having a higher education, using benzodiazepines, anxiety, and fatigue were all related to higher stress (van der Hiele, Spliethoff-Kamminga, Ruimschotel, Middelkoop, & Visser, 2012a).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, cross-sectional studies have established a link between heightened exposure to cumulative life stress and reduced memory performance in old age regardless of age or level of education (Dickinson et al, 2011;Tschanz et al, 2013). While presenting robust behavioral findings, the above cross-sectional studies fail to control for health behaviors that have been found to affect cognitive aging such as the amount of cigarette and alcohol consumption (Kalminjn et al, 2002), the amount of physical exercise (Kimura et al, 2013), or the presence of a physical disability.…”
Section: Introductionmentioning
confidence: 97%
“…WM is thought of as the brain's capacity to store and manipulate information necessary for successful performance in a given situation (Baddeley and Hitch, 1974) and has received large amounts of interest in the general aging and EEG literature. As such, a number of studies have demonstrated that the amount of items held in WM declines with advancing age (Salthouse and Babcock, 1991), whereas numerous EEG studies have reported age-related reductions of theta, alpha, and gamma activity during WM task engagement (Karrasch et al, 2004;Manard et al, 2014;van de Vijver et al, 2014).…”
Section: Introductionmentioning
confidence: 98%